KEPADATAN POPULASI KATAK SAWAH (Rana cancrivora Gravenhorst) YANG DITEMUKAN DI BUNGO PASANG KECAMATAN IV JURAI KABUPATEN PESISIR SELATAN - Yeni, Yulia Afrita (STKIP PGRI Sumbar, 2014)
Paddy frogs (Rana cancrivora Gravenhorst) is one type of frog is known by the public because in addition the meat can be eaten also are natural enemies of insects. Frogs are commonly found in paddy rice fields, paddy frogs are one of the animals that live in two worlds, namely water and land. Frog population at the present time are being lost. The use of pesticide impact on the environment by reducing the balance of the frog population density fields, the construction of settlements that cause the rice fields become small, so that disruption of habitats from lowland frogs. To determine the population density of paddy frog (Rana cancrivora Gravenhorst) were found in Bungo District of IV Jurai Attach the South Coastal District and find out the factors that influence population physics paddy frogs This study was conducted in August 2014. This study used a survey method (direct observation to the field ) using the line transect, the sampling technique using Systematic sampling method with a 100 m transect and plot number as many as 10 plots besides physics factor measurements performed 4 times sampling. Based on the research that has been done on Rice in Bungo Posting District of South Coastal District IV Jurai obtained Wetland Frogs population density is equal to 0.55 individuals / m2 and physical environmental factors at the time of sampling with a temperature of 25 Â° C and humidity of 65% -67%.